The world meets Asian tourists - Pearce, Philip L.; Wu, Mao-Ying (Emerald Group Publishing Limited, 2016)
The movement of Asian citizens across continents now occurs on an unprecedented scale, with a surge in Asian tourists now visiting Europe, North America, Africa and Oceania. Tourists from China, Taiwan, India, Thailand, Malaysia, and to a lesser extent Korea and Japan are meeting the citizens of cultures they had previously only been able to read about or view from afar. This book seeks to understand the experiences of, and reactions to, Asian tourists travelling out of Asia.Questions about Asian tourist contact with unfamiliar countries and cultures will be addressed. What are the interests of Asian tourists and what drives these interests? What impacts are they having on host communities, both in terms of the provision and co-creation of desired experiences and in the human dimensions of social contact? The volume addresses fresh implications for marketing, planning and policy which these tourist markets pose for good governance. This book confronts the limitations of our understanding of how to manage the tourist experience when that understanding has been built almost entirely on the behaviours and travels of western tourists.
Prelims -- Introduction -- Laws and regulations shaping outbound tourism -- Making sense of seasons -- Media representations of Chinese outbound tourists behavior -- Learning by and learning from outbound Chinese group tourists -- Managing Asian tourists on long-haul flights -- Thai tourists on tour -- Enclave resorts in Mauritius -- Italian cathedrals and Chinese tourists -- Australias food tourism experiences and the Korean market -- Theme parks greet Chinese tourists -- Cross cultural aspects of international guidebooks -- Communist connections? -- Interpreting Australian landscapes for Chinese tourists -- Talking about new chinese tourists -- Imagination, anime and Japanese tourists abroad -- Young Chinese tourists -- Singapore -- Conclusion -- About the authors -- References.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Industries -- Hospitality, Travel & Tourism; Tourism industry; Asians -- In mass media; Asians -- Public opinion; Tourists -- Public opinion